THE IMPACT OF DIVIDEND PAYOUT ON FUTURE EARNINGS GROWTH IN NON-FINANCIAL COMPANY LISTED IN INDONESIA STOCK MARKET (IDX) - Nugroho, Bernardus Yuliarto (Economic and Bussiness Faculty, Dr Soetomo University, 2019)
The purpose of this paper isÂ to examine the relation between Dividend Payout, Firm Size, ROA, Leverage, Earnings yield, Past Earnings Growth and Annual Growth in Total Assets towards Future Earnings Growth when the periode in one, three, and five years ahead. The study sample was taken from non-financial firms that listed on the Indonesia Stock Exchange in the period 2002-2016. The research method used in this research was multivariate regression. The proxy used forÂ variable dividend payout is dividend payout ratio and proxy used for variable earnings growth is compounded annual earnings per share. The result show that high dividends signal high earnings growth, so that the study weakens the point of view of previous market observers who argue that dividend has negative relations to future earnings growth. The results of this study can help investors in considering options in choosing companies to invest by choosing companies who have high dividends. Keywords - Dividend Payout; Size; Future Earnings Growth; Past Earnings Growth